1993
DOI: 10.1515/cclm.1993.31.12.811
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase in Human Semen: An Investigation Using Enzyme Inhibitors and Gel Electrophoresis

Abstract: Summary: Human seminal alkaline phosphatase was investigated with respect to its electrophoretic mobility, heat lability, and susceptibility to inhibition by phenylalanine, tartrate, and homoarginine. Total alkaline phosphatase activity in 30 samples of human semen was measured colorimetrically, using /?-nitrophenylphosphate as substrate. Using linear regression analysis, no significant correlation was found between the enzyme activity and the sperm count, sperm motility, semen volume, and the concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…It has been reported that human semen AP was totally inactivated by heating at 56 °C for 15 (Lewin et al ., ); accordingly, the ALP from boar seminal plasma analysed in this article showed a rapid decrease in activity at 60 °C, as already showed by Iyer et al . (), indicating similarity to human semen enzyme and to the bone ALP isoform.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that human semen AP was totally inactivated by heating at 56 °C for 15 (Lewin et al ., ); accordingly, the ALP from boar seminal plasma analysed in this article showed a rapid decrease in activity at 60 °C, as already showed by Iyer et al . (), indicating similarity to human semen enzyme and to the bone ALP isoform.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, we were also concerned about the status of seminal plasma alkaline phosphatase concentrations in IH-treated dogs. Dog's seminal plasma alkaline phosphatase is produced by the epididymis 6,7) and is found in high concentrations (i.e., Ͼ1000 IU/l) in normal ejaculates. 8) If the seminal plasma has a high alkaline phosphatase level but no spermatozoa, there is testicular spermatogenesis failure.…”
mentioning
confidence: 99%
“…AP has been found in the seminal plasma of humans (Lewin et al. ) and numerous animal species (Valiente et al. ; Kutzler et al.…”
Section: Discussionmentioning
confidence: 99%